Intestinal dysbiosis in heart failure - modulation of dysbiosis as a potential therapeutic target - Osiak, Joanna; Wołowiec, Łukasz; Żukow, Xawery; Fydrych, Dagmara; Jasniak, Albert; Gawłowska, Kinga; Staniewska, Agata; Grześk, Grzegorz (Journal of Education, Health and Sport, 2023)
The last decade has provided extensive information on the human gut microbiota. The microorganisms populating the gastrointestinal tract play important roles in maintaining the body's homeostasis. It turns out that the intestinal microbiota can affect many diseases from various branches of medicine. The importance of the function of the microflora can also affect cardiovascular diseases (CVD), including heart failure (HF). The microflora influences among other things, nutrient digestion, vitamin production or the production of bioactive metabolites including trimethylamine/trimethylamine N-oxide, short-chain fatty acids and bile acids. Therefore, changes in the composition of the intestinal microflora, defined as dysbiosis, have become one of the key pathogenic factors in many diseases. There is emerging evidence of a strong correlation between gut microflora and the occurrence of cardiovascular disease. In patients with cardiovascular disease and corresponding risk factors, the composition and proportions of the intestinal microflora differed significantly from healthy subjects. Differences in microbial composition and marked fluctuations in the levels of biomarkers such as TMAO, zonulin, LPS, SCFAs may become helpful in the diagnosis of cardiovascular diseases. For this reason, the intestinal microflora and its metabolic pathways have recently become the subject of numerous studies. A very important issue is the fact that it is possible to regulate the intestinal microflora through diet, the use of prebiotics, probiotics or influence through a much larger intervention - for example, fecal mass transplantation. These possibilities have become new strategies in the treatment of HF. The main purpose of this review is to summarize recent studies that illustrate the complex interactions between the microbiome and the occurrence of HF. Conclusions. The gut microbiota is a complex ecosystem of microorganisms that live in the human gut. The gut microbiota plays an important role in maintaining the body's health, including the cardiovascular system. Dysbiosis, or an imbalance in the gut microbiota, has been linked to the development of heart failure. Gut microbiota metabolites, such as trimethylamine N-oxide (TMAO), short-chain fatty acids (SCFAs), and bile acids, can have harmful effects on the heart. Diet, probiotics, and fecal microbiota transplantation (FMT) are all potential interventions for improving gut microbiota and reducing the risk of heart failure. More research is needed to fully understand the role of gut microbiota in heart failure and to develop effective treatment strategies.